STRUCTURAL AND FUNCTIONAL TRANSFORMATION OF ORGANIZATIONAL COMPETENCE OF OFFICIALS OF STATE AUTHORITY AND LOCAL SELF-GOVERNMENT IN WAR CONDITIONS - Danylenko, Lidiya; Dzeha, Volodymyr (Public Management and Policy, 2026)
The development of officials' organizational competence under difficult war conditions is a strategic task for the state, aimed at preserving institutional capacity and democratic principles of public administration. Modern civil servants must demonstrate leadership, independence, empathy, and initiative. The transformation of organizational competence of officials in wartime is a transition from bureaucratic to crisis management, focusing on speed of decision-making, digitalization of services, ensuring security and interaction with military administrations. The key competencies are stress resistance, adaptability, volunteer coordination skills and resource management in conditions of scarcity. In the context of leadership, the concept of management takes on a completely new meaning, because in this case, to achieve the outlined goal, not traditional management tools such as organization, planning, and control are used, but innovative approaches – analysis, motivation, and personal example. Decentralization processes in Ukraine have become a stimulus that involves focusing on using the potential of officials. The modern interpretation of organizational competence assumes formed skills of information processing using information and communication technologies and artificial intelligence. In this case, versions of the theory of organization, which studies the regularities of self-organization processes and self-forming factors, as well as the theory of systems (the content of integrity and systematicity), cybernetics (formation and transfer of guiding influences), synergetic (mechanisms of interaction of system elements in the process of self-organization and self-development) should be relevant.